Pulmonary Kaposi's sarcoma in patients with acquired immune deficiency syndrome: a clinicopathological study. Issue 4 (April 1987) - Fouret, P J; Touboul, J L; Mayaud, C M; Akoun, G M; Roland, J
Abstract : Pulmonary Kaposi's sarcoma may contribute to respiratory dysfunction in patients with acquired immune deficiency syndrome (AIDS) and features of pneumonitis. Opportunistic infections are readily recognised in endoscopic material, but pulmonary Kaposi's sarcoma is easily missed, so that patients are deprived of specific treatment. The clinical and pathological findings from nine cases of pulmonary Kaposi's sarcoma have been reviewed; these were found among 84 patients with AIDS and pneumonitis undergoing fibreoptic bronchoscopy and bronchoalveolar lavage. Diagnosis was established before death in eight patients (in five by bronchial biopsy and in three by open lung biopsy). Examination of lavage fluid showed alveolar haemorrhage in six patients. It is concluded that: (1) fibreoptic bronchoscopy may be useful in the diagnosis of endobronchial lesions of Kaposi's sarcoma; (2) alveolar haemorrhage in patients with AIDS is suggestive of pulmonary Kaposi's sarcoma. Factors that may cause difficulties in diagnosis include the focal nature of some lesions and the pleural or parenchymatous location of others. In addition, in the lung as in the skin, the early stages of Kaposi's sarcoma resemble granulation tissue. Such lesions are far more difficult to recognise than is the late nodular stage.